Comparison of Endoscopic Submucosal Dissection With Endoscopic Mucosal Resection After Circumferential Precutting to Treat Gastric Adenomas ≤15 mm - Jin Lee; Junghwan Lee; Ji Eun Na; Yong Eun Park; Joon Hyuk Choi; Nae-Yun Heo; Seung Ha Park; Tae Oh Kim; Jongha Park (Yong Chan Lee, 2024)
Objectives Endoscopic submucosal dissection (ESD) is a widely used approach for the resection of superficial gastric neoplastic lesions. Endoscopic mucosal resection (EMR) is acceptable for lesions <10-15 mm in size. Herein, we compared the clinical outcomes of ESD with those of EMR after circumferential precutting (EMR-P) for gastric adenomas ≤15 mm. Methods We retrospectively analyzed the data of 213 patients with 228 gastric adenomas ≤15 mm in size who were treated endoscopically at a single tertiary hospital in Korea between November 2018 and October 2022. We evaluated the complete endoscopic resection rate, recurrence rate, procedurer-elated complications, and procedure time according to the procedure used. Results Among the 228 gastric adenomas, 49 were treated with EMR-P and 179 with ESD. The histological complete resection rate was higher in the ESD group than in the EMR-P group (87% vs. 57%, p<0.001). No significant between-group differences were observed in endoscopic en bloc resection rates (ESD vs. EMR-P, 96% vs. 90%; p=0.081). The procedure time was significantly shorter in the EMR-P group than in the ESD group (28.9±19.7 min vs. 8.8±5.9 min, p<0.001). The local recurrence rate in patients with histologically incomplete resection did not differ between the two groups (ESD vs. EMR-P, 8.7% vs. 9.5%; p=0.924). Conclusions For gastric adenomas ≤15 mm, EMR-P may be the preferable treatment method considering the en bloc resection rate, procedure time, and local recurrence rate. However, considering the complete resection rate, ESD is recommended as the treatment of choice for high-grade adenomas and early gastric cancer lesions.